Influence of STEAM (Science, Technology, Engineering, Arts and Mathematics) Integration and Teaching Approaches on Pupils’ Engagement - Doncillo, Asterlin (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined how teachers’ STEAM integration and English teaching approaches influenced the learning engagement of Grade 3 pupils in selected public elementary schools in the Division of Butuan City during the school year 2025–2026. Anchored on Kolb’s (1984) Experiential Learning Theory, Fredricks, Blumenfeld and Paris’ (2004) Student Engagement Theory, and Bandura’s Social Cognitive Theory, the study employed a descriptive-correlational research design. Data were gathered from 200 Grade 3 pupils through structured survey questionnaires measuring STEAM integration, English teaching approaches, and pupils’ behavioral, emotional, and cognitive engagement. The instruments were validated, pilot-tested, and analyzed using descriptive statistics and multiple regression analysis. Findings revealed that teachers’ STEAM integration in English classes was highly implemented, with an overall mean of 4.22, while English teaching approaches were also rated high, with an overall mean of 4.36. Pupils’ learning engagement was likewise high, with an overall mean of 4.45. Regression results showed that STEAM integration and teaching approaches significantly influenced learning engagement, F(2, 197) = 67.529, p < .001, explaining 40.1% of the variance. Teaching approaches emerged as the stronger predictor. The study concluded that well-designed interdisciplinary and learner-centered English instruction supports pupils’ active participation, positive learning attitudes, and cognitive involvement. The study aligns with SDG 4 by supporting inclusive, equitable, and quality education through improved classroom instruction. Its sustainability impact lies in strengthening educational, technological, and institutional practices that promote engaging, innovative, and responsive learning environments.